PENGARUH KUALITAS WEBSITE LAZADA TERHADAP KEPUTUSAN PEMBELIAN ONLINE REMAJA SHOPAHOLIC DI PALEMBANG - Lina Lina (Jurnal Keuangan dan Bisnis, 2019)
This study aims to analyze the influence of Lazada's website quality on Shopaholic teenagers' online purchasing decisions in Palembang and analyze the differences between male and female participants in online purchasing decisions in Palembang. Shopaholic is defined as a tendency to shop compulsively with a high enough frequency. Shopaholic lifestyle teenagers spend a lot of time shopping as a saturation remover, as their satisfaction and more hanging out with people who have the same hobby in shopping. Shopping becomes a picture of consumptive behavior that is difficult to change. The positive impact as a stress reliever and to keep up with the times. While the negative impact is the formation of consumptive, wasteful, and addictive behavior. This study uses a combination of exploratory research and explanatory research. Exploratory research aims to explore the phenomenon of male and female differences in shopaholic teenagers' online purchasing decisions in Palembang. Explanatory research to explain the relationship between research variables, in this case, the influence of Lazada's website quality on online shopaholic teen purchasing decisions in Palembang. This type of research is survey research. The data collection technique is a survey by distributing questionnaires developed from previous research. The population is Teenagers who live in Palembang and have a shop online through the Lazada website. The sampling technique used purposive sampling with 138 respondents. Regression analysis is used to test the effect of Lazada's website quality on online purchasing decisions. The results showed that the influence of website quality lazada on shopaholic teenagers' online purchasing decisions was 73.6%, while 26.4% of purchasing decision variables were influenced by other variables outside of this study, including government policy variables, advertising socialization, and so on.